Persepsi Bank pada Pelaksanaan Restrukturisasi Kredit di Era Pandemi Covid-19 - Bekman Siagian; Endang Swasthika; Harya D Widiputra; Dyah N Taurusianingsih (Universitas Negeri Padang, 2022)
The Covid-19 pandemic has had a direct or indirect impact on banking. This study aims to investigate the conditions and perceptions of the banking industry in dealing with the Covid-19 pandemic and credit restructuring policies in Indonesia. This study is the result of a survey of 35 Perbanas member banks representing all bank groups based on their core capital. The results of the descriptive analysis found that the banking industry was quite strong, responded well to the shocks that occurred, and had strong optimism about the banking recovery. This condition is considered to support Indonesia's financial stability.